2022
DOI: 10.1002/ep.13835
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of products obtained of waste polyethylene terephthalate by pyrolysis

Abstract: In this study, waste polyethylene terephthalate (wPET) was converted to liquid fuel by the pyrolysis method. It was also investigated both effects of microwave pre‐treatment and catalyst (sodium borohydride) on total conversion and oil + gas yield. The reaction temperature of 375–425°C and the reaction time of 30 min are sufficient for the pyrolysis of waste plastic samples in a batch reactor. In the pyrolysis of wPETs, the highest oil + gas yield of 45% was obtained under the conditions of reaction temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…When compared with the GC–MS results of gasoline and diesel, it was observed that the obtained liquid products contained a few light components found in gasoline but were closer in content to diesel. This situation indicated that a product consisting of light compound components was obtained between gasoline and diesel (Olam and Karaca 2022 ). Considering the conversion rate, fuel properties, and the production of valuable chemicals, it was thought that this process would be feasible/applicable.…”
Section: Resultsmentioning
confidence: 98%
“…When compared with the GC–MS results of gasoline and diesel, it was observed that the obtained liquid products contained a few light components found in gasoline but were closer in content to diesel. This situation indicated that a product consisting of light compound components was obtained between gasoline and diesel (Olam and Karaca 2022 ). Considering the conversion rate, fuel properties, and the production of valuable chemicals, it was thought that this process would be feasible/applicable.…”
Section: Resultsmentioning
confidence: 98%
“…This product with high added value can be used to carry out new PET synthesis. Unlike other methods examined in the literature [ 34 ], HTL allows the conversion of PET into terephthalic acid with high yields by working at lower temperatures and in the absence of a catalyst, which would contaminate the solid phase. Furthermore, compared to other HTL studies [ 17 ], the process conditions were optimized, obtaining the same yield of terephthalic acid but carrying out the reactions for shorter times.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrolysis is one of the main methods of MSW resource utilization that can convert organic matter into small-molecule combustible gas and liquid oil in an inert environment while solidifying heavy metals into char [3]. Compared with incineration, pyrolysis is a relatively uncomplicated technology requiring no complex processing plant, it is quite environmentally friendly, and the process parameters are controlled according to the desired products [4][5][6].…”
Section: Introductionmentioning
confidence: 99%